Subserratus Anterior Plane Block vs Thoracic Paravertebral Block for Postoperative Analgesia in Laparoscopic Radical Nephrectomy: Protocol for a Randomized Controlled, Double-Blind, Non-Inferiority Clinical Trial - Lin J; Wu H; Wen Z; Li Y; Jiang C; Lin B; Gu Y (Journal of Pain Research)
Jianghuai Lin,1 Huanghui Wu,2 Zhibin Wen,3 Yangyi Li,1 Changcheng Jiang,1 Binghong Lin,4 Yu Gu5 1Department of Anesthesiology, Quanzhou First Hospital Affiliated to Fujian Medical University, Quanzhou, Fujian Province, 362000, People’s Republic of China; 2Department of Anesthesiology and Perioperative Medicine, Shanghai Fourth People’s Hospital, School of Medicine, Tongji University, Shanghai, 200434, People’s Republic of China; 3Graduate School of Fujian Medical University, Fuzhou, Fujian Province, 350122, People’s Republic of China; 4Graduate School of Victoria University of Wellington, Wellington, 6014, New Zealand; 5Department of Anesthesiology, Zigong Fourth People’s Hospital, Zigong, Sichuan Province, 643000, People’s Republic of ChinaCorrespondence: Yu Gu, Department of Anesthesiology, Zigong Fourth People’s Hospital, Zigong, Sichuan Province, People’s Republic of China, Email guyu951221@163.comIntroduction: Thoracic paravertebral nerve block (TPVB) is a widely used regional anesthesia technique employed in opioid-sparing anesthesia for abdominal surgery. Although the subserratus anterior plane block (SSAPB) has shown effectiveness in providing analgesia in upper abdominal surgery, it remains unclear whether the SSAPB offers comparable analgesic effects to the TPVB for retroperitoneal laparoscopic nephrectomy.Methods and Analysis: This study is designed as a prospective, randomized controlled, double-blind, single-center, non-inferiority trial involving a total of 106 patients undergoing retroperitoneal laparoscopic nephrectomy. Participants will be randomly assigned to either the SSAPB group or the TPVB group in a 1:1 ratio. Both ultrasound-guided SSAPB and TPVB will involve the administration of 0.375% ropivacaine at a dose of 0.4 mL/kg prior to anesthesia induction. Subsequently, opioid-sparing anesthesia will be utilized during surgery. Each patient will receive standardized patient-controlled intravenous analgesia (PCIA) without a background infusion. The primary outcome measure will be the 24-hour postoperative consumption of rescue opioids. Secondary outcomes will include pain visual analogue scale (VAS) scores at various predefined time points within 48 hours post-surgery, analgesic consumption during and after surgery, time to first administration of rescue analgesics, incidence of perioperative cardiopulmonary adverse events, assessment of block characteristics, quality of recovery, time to ambulation and initiation of an oral diet, and length of stay in both the postoperative anesthesia care unit (PACU) and the hospital. Additionally, levels of inflammatory markers, including interleukin-6 (IL-6) and C-reactive protein (CRP), will be assessed at predefined time points.Discussion: This protocol outlines the first prospective, randomized controlled, double-blinded, non-inferiority clinical trial comparing perioperative analgesic efficacy and safety of SSAPB versus TPVB in patients undergoing retroperitoneal laparoscopic nephrectomy under opioid-sparing anesthesia. The study is designed to generate preliminary insights into optimizing regional anesthesia strategies for perioperative pain management in this surgical cohort.Keywords: thoracic paravertebral nerve block, subserratus anterior plane block, laparoscopic radical nephrectomy, opioid-sparing anesthesia